Design and modeling of a virtual PA-10 robot for surgical applications - Fernández-Riomalo, Carlos Eduardo; Guástar-Morillo, Héctor Andrés; Vivas-Albán, Oscar Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper shows the implementation of a PA-10 Mitsubishi robot on a surgical virtual simulator for laparoscopic surgeries by using surgical assistant robots. For the proposed simulator three robots are necessary: An endoscope-holder robot (in this case the Hibou robot), and two surgical robots (in this case a Lapbot robot and the designed PA-10 robot). The three robots are manipulated by a joystick device on a gallbladder ablation exercise (cholecystectomy). Deformation algorithms are included to provide greater realism, when the end-effector of the robot collides with the PA-10 virtual robot, abdominal organ. Results provide the base of a surgical virtual simulator using three assistant robots on a common laparoscopic surgical exercise, that can be used for training new surgeons.